ANALYSIS AND MAPPING OF LOG ERRORS IN ACTIVE DIRECTORY IN AREAL PRODUCTION ENVIRONMENT: A CASE STUDY IN COMPANY USINASITAMARATI (UISA) (REMUNOM, 2025)
In corporate networks, Active Directory (AD) is one of the main tools for managing, centralizing, and authenticating user and service access. In this context, mapping the main errors related to AD is essential to prevent future failures. This article presents a case study at Alfa Company, which has 4,000 users in AD, based on the analysis of logs collected between January 2022 and December 2023. Thus, the 10 most frequent errors were identified and classified into two categories: Application Logs and System Logs. Each error was mapped, categorized, and represented by graphs and tables, considering type, class, frequency, affected user profile, and possible solutions. The results demonstrate that the systematization of errors contributed significantly to identifying recurring failures, assessing impacts on the corporate environment, and developing practical and effective solutions